Cross-hierarchical plasticity of corticofugal projections to dLGN after neonatal monocular enucleation - Giasafaki, C; Grant, E; Hoerder-Suabedissen, A; Hayashi, S; Lee, S; Molnár, Z (Wiley, 2022)
Perception is the result of interactions between the sensory periphery, thalamus, and cerebral cortex. Inputs from the retina project to the first-order dorsal lateral geniculate nucleus (dLGN), which projects to the primary visual cortex (V1). In return, the cortex innervates the thalamus. While layer 6 projections innervate all thalamic nuclei, cortical layer 5 neurons selectively project to the higher order lateral posterior nucleus (LP) and not to dLGN. It has been demonstrated that a subpopulation of layer 5 (Rbp4-Cre+) projections rewires to dLGN after monocular or binocular enucleation in young postnatal mice. However, the exact cortical regional origin of these projections was not fully determined, and it remained unclear whether these changes persisted into adulthood. In this study, we report gene expression changes observed in the dLGN after monocular enucleation at birth using microarray, qPCR at P6, and in situ hybridization at P8. We report that genes that are normally enriched in dLGN, but not LP during development are preferentially downregulated in dLGN following monocular enucleation. Comparisons with developmental gene expression patters in dLGN suggest more immature and delayed gene expression in enucleated dLGN. Combined tracing and immuno-histochemical analysis revealed that the induced layer 5 fibers that innervate enucleated dLGN originate from putative primary visual cortex and they retain increased VGluT1+ synapse formation into adulthood. Our results indicate a new form of plasticity when layer 5 driver input takes over the innervation of an originally first-order thalamic nucleus after early sensory deficit.